KEPEMIMPINAN VISIONER KEPALA SEKOLAH DALAM MENGEMBANGKAN BUDAYA ISLAMI DI SDS IT SULTHONIYAH SAMBAS - Bekti Pratiwi; Hifza, Topik (ADISAM PUBLISHER, 2025)
Developing Islamic culture in s chools means instilling in children good habits that are in line with Islamic values which are manifested in the way s tudents act and behave. The s chool principal feels it is very necessary to develop these Islamic values and make them a way of life and a guide to behavior. This research was designed using a qualitative approach method and a case s tudy type of research. The data collection techniques are observation, interviews and documentation. The data analysis techniques used are data collection, data reduction, data display, and drawing conclusions. The results of this research show that: (1) the visionary leadership competency possessed by the s chool principal is being able to realize the vision, being a good communicator, having clear leadership targets, being adaptive, and having the e ffort to provide the best s chool s ervices, (2) the role of visionary leadership The principal in developing an Islamic culture, namely determining s teps and s trategies to achieve s chool goals, anticipating various policy changes, e s tablishing communication and building relationships with internal and external s chools, and trying to be a good role model for the s chool community, (3 ) the implications of the s chool principal's visionary leadership for Islamic culture, namely the habituation of Islamic values which are based on the s chool's vision and mission, the creation of an Islamic climate by preparing habituation programs, carrying out regular monitoring and evaluation, and reminding teachers to continue to provide good examples for children and always optimistic in carrying out their roles